Міфолого-релігійні джерела фразеологічних одиниць із компонентом темрява - Лебедєва, Т. (Лексикографічний бюлетень, 2011)
In the article, phraseological units with component symbol darkness are investigated in ethnolinguistic aspect. The data investigated shows the remoteness, universality and cogency of this symbol for human consciousness. Four thematic groups of PU with the component darkness have been selected and analysed, representing mythological and religious conception darkness as source of life, death, embodiment of sinfulness, ignorance, misunderstanding. It is found out, that symbol darkness as a component of PU makes up culturally meaningful unit, interpreting such spheres of vital activity of man, as: ontological (darkness is related to death); gnosiological (darkness as vagueness, uncertainty); religious (darkness is Divine punishment, personifies dark, devil forces, sin, disbelief ).